Functional lightweight protective clothing shielding design for constant radiation shielding of flight attendants and Monte Carlo simulation verification - Kim, Seon-Chil; Youn, Sukwon (Frontiers in Materials, 2023)
The use of easily accessible shielding suits for personal defense by flight attendants to reduce occupational cosmic radiation exposure is attracting increasing attention. However, to ensure activity in a limited area, the flexibility of the thin film must be considered. Although several process technologies to reduce the thickness of the shielding fabric are available, nanofiber production through electrospinning is the most effective, and it is attracting attention owing to its excellent reproducibility of the shielding performance. Therefore, in this study, a general sheet and a nanofiber shielding sheet were manufactured, and their shielding performance was compared. In addition, the shielding effect of the nanofiber shielding sheet was verified under aircraft conditions via Monte Carlo simulation. The shielding performance for neutrons and gamma rays, which are the most common sources of cosmic radiation, was 17.5% and 15.2%, respectively, with the Ba-133 and Cs-137 sources in the 0.3 mm shielding fabric. The absorbed dose change with the 5 mm shielding fabric was 7 µGy/d for neutrons and 4.3 µGy/d for protons. The shielding fabric developed in this study is expected to have an active shielding effect when used as personal protective equipment (clothing) by aircrew.